1990
DOI: 10.1021/bi00501a016
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyl radical induced cleavage of disulfide bonds in proteins. A .gamma.-ray and pulse radiolysis mechanistic investigation

Abstract: Disulfide bond reduction by the CO2.- radical was investigated in aponeocarzinostatin, aporiboflavin-binding protein, and bovine immunoglobulin. Protein-bound cysteine free thiols were formed under gamma-ray irradiation in the course of a pH-dependent and protein concentration dependent chain reaction. The chain efficiency increased upon acidification of the medium, with an apparent pKa around 5, and decreased abruptly below pH 3.6. It decreased also at neutral pH as cysteine accumulated. From pulse radiolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 55 publications
(65 reference statements)
2
88
0
Order By: Relevance
“…The absorption coefficient of the disulphide radical at between 410 nm and 425 nm, " [410][411][412][413][414][415][416][417][418][419][420][421][422][423][424][425] , is estimated to be 4000-9000 M À1 cm À1 (Favaudon et al, 1990). If the sample is assumed to be uniform, the thickness is taken to be between 50 and 100 mm and the absorbance of the irradiated crystal to be around 0.5, the concentration of this radical may be estimated at between 35 mM (using 4000 M À1 cm À1 and 50 mm) and 8 mM (using 9000 M À1 cm À1 and 100 mm).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption coefficient of the disulphide radical at between 410 nm and 425 nm, " [410][411][412][413][414][415][416][417][418][419][420][421][422][423][424][425] , is estimated to be 4000-9000 M À1 cm À1 (Favaudon et al, 1990). If the sample is assumed to be uniform, the thickness is taken to be between 50 and 100 mm and the absorbance of the irradiated crystal to be around 0.5, the concentration of this radical may be estimated at between 35 mM (using 4000 M À1 cm À1 and 50 mm) and 8 mM (using 9000 M À1 cm À1 and 100 mm).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…From previously reported work (Favaudon et al, 1990), this was identified as the disulfide radical anion (RSSR À ) that is elongated by 0.7 Å with respect to a neutral disulfide bond (Weik et al, 2002). This peak was present in irradiated crystalline samples of the disulfide-containing proteins that were examined: lysozyme (244 mM S-S bond concentration), bovine trypsin (192 mM), N9 neuraminidase (120 mM), but not in apoferritin which, although it has no disulphides, has two cysteines (52 mM cysteine) per monomer.…”
Section: Disulfide-containing Proteinsmentioning
confidence: 99%
“…The carboxyl anion radical is also formed by water radiolysis in the presence of formate ions or by photoreduction of carbon dioxide. [29,30] If this is the case, the exothermic peak which has appeared at the temperature higher than 100 8C might be associated with the doping reaction. The shift of the exothermic peak to higher a temperature with increasing F ( Figure 5 a) suggests that doping becomes more difficult to occur when the AA3T content in the copolymer increases.…”
Section: Thermal Behaviormentioning
confidence: 99%
“…Pulse radiolysis experiments have revealed that the disulfide radical anion and its protonated form absorb with maxima at 425-440 nm and 400 nm, respectively (Favaudon et al, 1990;Armstrong, 1990). In a study by Weik et al (2002), the observed maximum at 400 nm in the absorption spectrum from X-ray-exposed native Torpedo californica acetylcholinesterase crystals was identified as being from a disulfide radical anion species.…”
Section: Disulfide/thiol Test Systemsmentioning
confidence: 99%